Baseline concentrations, spatial distribution and origin of trace elements in marine surface sediments of the northern Antarctic Peninsula ... - Delhaye Louise, J.; Elskens Marc; Ricaurte-Villota Constanza; Cerpa Luis; Kochzius Marc (Zenodo, 2023)
Supplementary data to article published in Marine Pollution Bulletin 187 (2023) 114501: https://doi. org/10.1016/j.marpolbul.2022.114501 ...